1995
DOI: 10.1083/jcb.129.6.1691
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-anchored heparin-binding EGF-like growth factor (HB-EGF) and diphtheria toxin receptor-associated protein (DRAP27)/CD9 form a complex with integrin alpha 3 beta 1 at cell-cell contact sites.

Abstract: Abstract. Heparin-binding epidermal growth factorlike growth factor (HB-EGF) is a member of the EGF family of growth factors, which interact with EGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
176
0
3

Year Published

1997
1997
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(191 citation statements)
references
References 57 publications
12
176
0
3
Order By: Relevance
“…TM4SF and integrin ␣3 create a complex form in normal tissue. 25 However, our results have shown that this complex has broken down and the relationship is not present in colon cancer progression. It was thought that the change of complex composed of integrin ␣3…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…TM4SF and integrin ␣3 create a complex form in normal tissue. 25 However, our results have shown that this complex has broken down and the relationship is not present in colon cancer progression. It was thought that the change of complex composed of integrin ␣3…”
Section: Discussionmentioning
confidence: 59%
“…[22][23][24] On the other hand, it was reported that integrin ␣3␤1 forms a complex with MRP-1/CD9 that colocalizes at the cell-cell contact site. 25 In addition, KAI1/CD82 is associated constitutively with integrin ␣3␤1. 26 Therefore, TM4SF forms membrane complexes with integrin receptors and is implicated in integrin-mediated cell migration.…”
mentioning
confidence: 99%
“…Members of the transmembrane-4 superfamily (or tetraspan superfamily) of membrane proteins, which includes CD9 , are frequently found within such complexes, where they are thought to participate in receptor signalling (reviewed by Wright and Tomlinson, 1994). The B-cell and T-cell antigen receptors are particularly good examples of such multicomponent structures (Matsumoto et al, 1993 ;Imai et al, 1995).Integrin heterodimers can form complexes with other membrane proteins, including a transmembrane-4 protein, CD9 (Slupsky et al, 1989;Rubinstein et al, 1994;Nakamura et al, 1995). Thus, in stimulated platelets, the principal integrin, glycoprotein (gp)IIb/IIIa (also known as a , r h /~3 , CD41/CD61), has been shown by chemical cross-linking to be associated with CD9 (Slupsky et al, 1989).…”
mentioning
confidence: 99%
“…Interestingly, multiple studies indicate CD9 clusters at cell-cell contacts in a variety of cell types (Gordon-Elonso 2006, Nakamura 1995. It is interesting that CD9 was not found to localize to platelet-matrix contact sites on any of the matrices studied (Fig 4.5).…”
Section: Localization and Protein Partners Of Cd9mentioning
confidence: 94%
“…This phenomena is observed both in cells natively expressing CD9, such as kidney epithelium and breast cancer cells, (Nakamura 1995) and in cells that have been transfected with CD9 . Additionally, CD9, CD81, and CD151, along with integrins, accumulate at keratinocyte cell junctions (Penas 2000).…”
Section: Cell-cell Interactionsmentioning
confidence: 99%